Analysis and Investigation of the Articles in the Journal of Geography and Planning during 2010-2014 Recorded in Islamic World Science Citation Center - Fatemeh Alinejad Chamazkoti; Saeedeh Mirhaghjoo Langroodi (نشریه جغرافیا و برنامه‌ریزی, 2016)
Scientific capacity is one of the key factors contributing to sustainable development in a country. The development of scientific capacity requires improvement in scientific publication and productions. This study aimed to investigate the publishing condition of the articles in the Journal of Geography and Planning during 2010-2014. The study adopted a descriptive method and survey design. The results showed that the Journal has published a number of 201 articles over the studied period. Of the published articles, 87% were co-authored by multiple writers. The co-authorship was mostly in the form of intra-institutional contribution. The mean score of collaboration degree was 0.87 while the mean score of collaboration index was shown to be 2.53, which indicates strong co-authorship relations among the Journal contributors. The highest collaboration percentage was observed between two and three authors. With 97 articles, the authors affiliated with TabrizUniversity published about 50% of articles in the Journal. Thus, TabrizUniversity was the most prolific institution.